Beam-wave interaction in periodic and quasi-periodic structures - Schächter, Levi; SpringerLink (Online service). (Berlin New York Springer, 2011)
The main theme of this book is the interaction of electrons with electromagnetic waves in the presence of periodic and quasi-periodic structures in vacuum, in view of applications in the design and operation of particle accelerators. The first part of the book is concerned with the textbook-like presentation of the basic material, in particular reviewing elementary electromagnetic phenomena and electron dynamics. The second part of the book describes the current models for beam-wave interactions with periodic and quasi-periodic structures. This is the basis for introducing, in the last part of the book, a number of particle and radiation sources that rest on these principles, in particular the free-electron laser, wake-field acceleration schemes and a number of other advanced particle accelerator concepts. This second edition brings this fundamental text up-to-date in view of the enormous advances that have been made over the last decade since the first edition was published. All chapters, as well as the bibliography, have been significantly revised and extended, and the number of end-of-chapter exercises has been further increased to enhance this book?s usefulness for teaching specialized graduate courses.
Introduction -- Elementary Electromagnetic Phenomena -- Elementary Electron Dynamics -- Models of Beam-Wave Interaction in Slow-Wave Structure -- Periodic Structures -- Quasi-Periodic Structures -- Free-Electron Laser -- Basic Acceleration Concepts -- References -- Subject Index.
Electronic reproduction.
Keywords: Electron beams; Particles (Nuclear physics); Electronic books